The Influence of Fashion Product Packaging on the Shopee Platform Toward Consumer Satisfaction and Loyalty among Generation Z - Rannia, Yovita Yvi; Syarief, Achmad (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of fashion product packaging on the Shopee platform on consumer satisfaction and loyalty among Generation Z. With the increasing competition in the e-commerce market, especially in the fashion segment, product packaging plays a crucial role in creating a satisfying shopping experience for consumers. Using a quantitative approach, this research distributed questionnaires to Generation Z consumers to identify which packaging design elements most significantly affect satisfaction and loyalty. The packaging design elements analyzed include shape, color, typography, and product information. The findings show that packaging design has a significant impact on consumer satisfaction, with an R Square value of 84.6%, indicating that packaging design explains a majority of the variation in consumer satisfaction. Furthermore, regression results also reveal that packaging design positively influences consumer loyalty, with an R Square value of 79.8%. Packaging elements such as easy-to-read typography and attractive colors were found to significantly influence consumers’ perceptions of fashion product quality on Shopee. Consumers tend to be more loyal and satisfied with products that are well-packaged, aesthetically pleasing, and ensure product safety during delivery. Thus, this study provides insights into the importance of packaging design strategies in maintaining consumer satisfaction and loyalty among Generation Z on e-commerce platforms like Shopee. Recommendations are given to businesses to continue optimizing the visual and functional aspects of their product packaging to remain competitive in the online market.